The Relevance of The Human Development Index from An Islamic Perspective to Macroeconomics and Zakat: A Measure of The Development of The World's Muslim Community - Hasbi, M. Zidny Nafi’ (Muslim Business and Economics Review, 2023)
This paper analyses the core concepts and indicators of the Human Development Index (HDI) from a religious and theological perspective, particularly from an Islamic perspective (termed I-HDI). By using the theory of maqāṣid al-sharīʿah (the goals or objectives of Islamic law), this study looks at how I-HDI, macroeconomics, and zakat (alms) are interrelated. The study then tests the HDI and IHDI calculations and analyses for differences and similarities between them. This research uses the dynamic panel regression method with generalised method of moments (GMM) analysis in two steps. The author found that HDI and I-HDI provide very different results. The results of the HDI calculation are in the middle to lower ranking on the scale, while I-HDI sits on the upper middle scale. There is a large disparity between the results of HDI and I-HDI calculations. Hypothesis testing shows a positive macroeconomic relationship and influence on I-HDI, while the zakat variable is detrimental to I-HDI. This condition occurs because the strategy and management of zakat by the government is not optimal.